A New Regional Cold War in the Middle East and North Africa: Regional Security Complex Theory Revisited. Issue 4 (2nd October 2017) - Hanau Santini, Ruth
Abstract: Since the 2003 Iraq war, the Middle East and North Africa has entered into a New Regional Cold War, characterised by two competing logics: on the one hand, the politicisation of sectarianism opposing a Saudi-led Sunni bloc against an Iran-led Shia bloc and, on the other, an intra-Sunni cleavage around the mobilisation of political Islam, embodied by the Muslim Brotherhood and its supporters vs its opponents. Blending Buzan and Weaver's regional security complex theory with Donnelly's notion of 'heterarchy' and applying it to the cold wars the region has experienced, the similarities and differences between the Arab Cold War of the 1950s/60s and the New Regional Cold War reveal the increasing number of heterarchic features within the regional security complex: multiple and heterogeneous power centres, different power rankings, a more visible and relevant role of non-state and transnational actors, and the fragmentation of regional norms.